An Investigation on Key Factors Influencing Consumers’ Green Purchase Behavior in Zhengzhou, China - Kang, Jing (Scholar: Human Sciences, 2025)
Purpose: This research identifies and analyzes the factors influencing consumers’ green purchase behavior in Zhengzhou, China, focusing on elements like environmental concern, attitudes towards green products, and perceived behavioral control. Research Design, Data, and Methodology: Employing a quantitative research design, the study used a structured questionnaire to explore relationships among key constructs related to green purchase behavior. The population consisted of 450 residents from Zhengzhou’s eight main districts, all with prior experience purchasing green products. Sampling techniques included judgmental, quota, convenience, and snowball sampling. Validity and reliability were assessed using the index of item objective congruence (IOC) and Cronbach’s Alpha from a preliminary sample of 50 respondents. After data collection, confirmatory factor analysis (CFA) and structural equation modeling (SEM) validated the measurement model and relationships among constructs. Results: The analysis revealed significant positive correlations among the constructs, highlighting the importance of environmental concern and positive attitudes towards green products in shaping both green purchase intention and actual behavior. Conclusions: The study concludes that enhancing environmental awareness and education is vital for promoting green consumption in Zhengzhou. It suggests that policymakers and marketers should focus on these areas, while also recommending further research to explore these dynamics in different contexts to better understand consumer behavior toward green products.